Experience of propofol sedation in a UK ERCP practice: lessons for service provision. Issue 1 (10th September 2014) - Joshi, D; Paranandi, B; El Sayed, G; Down, J; Johnson, G J; Chapman, M H; Pereira, S P; Webster, G J M
Abstract : Objective: Endoscopic retrograde cholangiopancreatography (ERCP) in the UK has been historically performed under conscious sedation. However, given the increasing complexity of cases, the role of propofol-assisted ERCP (propERCP) is increasing. We describe our experience of propERCP and highlight the importance of this service. Design: Our prospective ERCP database was interrogated between January 2013 and January 2014. Data collection included procedural information, patient demographics, American Association of Anaesthesiologists (ASA) status, Cotton grade of endoscopic difficulty and endoscopic and anaesthetic complications. Comparison was made with patients undergoing conscious sedation ERCP (sedERCP). Results: 744 ERCPs were performed in 629 patients (53% male). 161 ERCPs were performed under propofol. PropERCP patients were younger compared with the sedERCP group (54 vs 66 years, p<0.0001) but ASA grade 1–2 status was similar (84% vs 78%, p=0.6). An increased number of Cotton grade 3–4 ERCPs were performed in the propERCP group (64% vs 34%, p<0.0001). Indications for propERCP included sphincter of Oddi manometry (27%), previously poorly tolerated sedERCP (26%), cholangioscopy (21%) and patient request (8%). 77% of cases were elective, 12% were urgent day-case transfers and 11% were urgent inpatients. 59% of cases were tertiary referrals. ERCP was completed successfully in 95% of cases. Anaesthetic and endoscopic complications were comparable between the two groups (5% and 7% vs 3% and 5%). Where sedERCP had been unsuccessful due to patient intolerance, the procedure was completed successfully using propofol. Conclusions: PropERCP is safe and is associated with high endoscopic success. The need for propERCP is likely to increase given patient preference and the high proportion of complex procedures being undertaken. All endoscopy units should look to incorporate propofol-assisted endoscopy into aspects of their services.